Respuestas
Respuesta dada por:
6
x(x+2)= 4x
![{x}^{2} + 2x = 4x {x}^{2} + 2x = 4x](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%2B+2x+%3D+4x)
![{x}^{2} = 4x - 2x {x}^{2} = 4x - 2x](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%3D+4x+-+2x)
![{x}^{2} = 2x {x}^{2} = 2x](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%3D+2x)
![{x}^{2} \div 2x {x}^{2} \div 2x](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%5Cdiv+2x)
![x = 2 x = 2](https://tex.z-dn.net/?f=x+%3D+2)
Respuesta dada por:
12
Respuesta:
Las dos soluciones son
x₁ = 0 ; x₂ = 2
Explicación paso a paso:
x ( x + 2 ) = 4x
x² + 2x = 4x
x² + 2x - 4x = 0
x² - 2x = 0 factorizamos
( x ) ( x - 2 ) = 0 igualamos los factores a cero
x₁ = 0
x₂ - 2 = 0
x₂ = 2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años